Capacity Building of Residents In Utilizing Family Medicinal Plants as an Alternative To Self-Medication - Dini Rudini; Fadliyana Ekawaty; Putri Irwanti Sari; Yulia Indah Permata Sari; Yosi Oktarina (International Journal Of Community Service, 2024)
The utilization of Family Medicinal Plants (TOGA) as an alternative for self-medication has the potential to improve community health and well-being. This community service program aimed to enhance the capacity of residents in Penyengat Rendah Village in utilizing TOGA. The program involved training, mentoring, and the provision of simple technologies to support the effective cultivation and processing of medicinal plants. The results showed a significant increase in residents' knowledge and skills, with the average score increasing from 48 in the pre-test to 90 in the post-test (p < 0.001). The effect size (d = 2.3) indicated a substantial impact of the intervention on participants' knowledge improvement. Regression analysis revealed that the pre-test score only explained 10.71% of the post-test score variance, suggesting the influence of other factors on learning outcomes. The application of relevant technologies, such as drying racks and digital education platforms, contributed to the program's effectiveness. Through active community participation and appropriate technology, this program has the potential to become a sustainable health solution and economic resource. Further development of the program is recommended, including advanced processing techniques, the formation of TOGA communities, and collaboration with local markets to enhance the economic value of TOGA products.